Diagnostic Value of CT Angiography (CTA) in Carotid Cavernous Fistula (CCF) Patients Using the Digital Subtraction Angiography (DSA) as The Gold Standard: Observation in Dr. Soetomo General Hospital Surabaya from January 2016 to July 2020 - Laila Amalia; Hartono Yudi Sarastika; Bambang Soeprijanto (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Background: CT angiography (CTA) is the initial modality for diagnosing the Carotid Cavernous Fistula (CCF), identifying the type of CCF, measuring the diameter of the fistula and the diameter of the internal carotid artery (ICA) pre and post fistula, and then confirmed by Digital Subtraction Angiography (DSA) as the gold standard. CTA is expected to provide more information to improve the accuracy of CCF diagnosis to benefit therapy and prevent complications. This study aimed to determine the diagnostic value of CTA in CCF patients in Dr. Soetomo General Hospital Surabaya, using the DSA as a gold standard. Methods: An observational retrospective study of CCF patients met the inclusion and exclusion criteria and underwent CTA and DSA examinations at the Radiology Installation of Dr. Soetomo General Hospital, Surabaya, from January 2016 to July 2020. Results: In the comparison of types of CCF CTA to DSA, the direct group was 53.8% and 57.7%, respectively, while the indirect group was 46.1% and 42.3% with a very strong correlation (κ = 0.922; p = 0.000), sensitivity was 93.3%, specificity was 100 %, PPV of 100%, NPV of 91.7% and accuracy of 96.15%. Direct type evaluation on the DSA showed a large picture of the fistula diameter; the ICA pre fistula's size was enlarged; therefore, the ICA post fistula diameter was reduced or absent. There was a strong correlation of fistula diameter measurement results between CTA and DSA (r = 0.695, p = 0.006). Conclusion: CTA has a similarity rate of 92.2% with DSA in identifying the type of CCF. The accuracy value of CTA is close to DSA in fistula diameter measurements.